Shielding of virus-like nanoparticles of hepatitis B core antigen by poly(2-oxazoline) for reduced antigenicity - Fam, See Yee (2021)
The rapid advances of nanotechnology over the past decades have led to increasing development of nano-sized drug delivery systems for various biomedical applications, including cancer therapies. Virus-like nanoparticles (VLNPs) have received considerable interest as nanocarriers for targeted drug delivery to cancer cells. This is owing to their numerous advantages over synthetic nanomaterials, including their biocompatible and biodegradable properties as well as their distinct interfaces for functionalization. Despite the remarkable features, VLNPs have intrinsic drawbacks, in particular, potential antigenicity and immunogenicity, which hamper their clinical applications in nanomedicine. Thus, they can be eliminated easily and rapidly by the host immune systems upon administration, rendering these nanoparticles ineffective for drug delivery to the target site. Recombinant hepatitis B core antigen (HBcAg) VLNPs have been widely employed as a smart drug delivery system as their large surface area exposes numerous amino acid residues for bioconjugation and cross-linking of therapeutic agents. However, HBcAg VLNPs are highly antigenic and immunogenic, compromising their drug delivery efficacy for cancer treatments. The aim of this study was to reduce the antigenicity of HBcAg VLNPs by shielding them with a hydrophilic polymer, poly(2-ethyl-2-oxazoline) (PEtOx). In the present study, an amine-functionalized PEtOx (PEtOx-NH2) was synthesized using the living cationic ring-opening polymerization (CROP) technique and characterized by nuclear magnetic resonance (NMR) and mass spectrometry (MS). The synthesized PEtOx-NH2 was then covalentlyconjugated to HBcAg VLNPs via carboxyl groups. The PEtOx-conjugated HBcAg (PEtOx-HBcAg) VLNPs were characterized with dynamic light scattering and UV-visible spectroscopy. The colloidal stability study indicated that both HBcAg and PEtOx-HBcAg VLNPs maintained their particle size in Tris-buffered saline (TBS) at human body temperature (37°C) for at least five days. Enzyme-linked immunosorbent assay (ELISA) also demonstrated that the antigenicity of PEtOx-HBcAg VLNPs reduced significantly as compared with unconjugated HBcAg VLNPs, indicating that the external surface of HBcAg VLNPs shielded by PEtOx exhibits a stealth behavior that restrains the binding of antibody to the nanoparticles. This novel surface functionalization with PEtOx provides a general platform for resolving the antigenicity of VLNPs, enabling them to be developed into a variety of powerful drug deliveries in nanotechnology with the ability to evade the immune surveillance. These PEtOx-HBcAg VLNPs could serve as a promising candidate for targeted drug delivery in animal and clinical studies.